The Moral Values Included in the English Textbooks of the Secondary school in Jordan - Nairoukh, Nour"MohammedTharief"; Abu Sneineh, Odeh Abdel- Jawad (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to reveal the moral values included in the English textbooks of the secondary school in Jordan, analyzing the content of these books to answer the questions of this study To achieve this, the descriptive analytical approach was used, The tool represented in building a list of the moral values that included (4) main domains, they are: individual, family, societal, and international moral values, and (40) minor moral values that were applied to a sample of two English books consisted of four parts. The reliability coefficient of the tool was (93.3) according to Holisti equation. The results revealed that the total repetitions of moral values in the English language textbooks for the 11th grade as a whole, amounted to (477) recurrences and a percentage (50.64%) of the total repetitions in the two English language textbooks for the secondary stage as a whole, which is within the limits of the large degree of inclusion. The results showed that the total frequency of moral values in the English language textbooks for the 12th grade as a whole, amounted to (465) recurrences and a percentage of (49.36%) of the total repetitions in the two English language books for the secondary stage, a percentage, which is within the limits of the large degree of inclusion.